2014
DOI: 10.1097/mol.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Updates on apolipoprotein CIII

Abstract: Recent data further strengthen the theory that apoCIII exerts strong atherogenic functions through both indirect and direct mechanisms. Encouraging results from early stage clinical trials demonstrate that modulating apoCIII per se is a novel and potent therapeutic approach to managing dyslipidemia and cardiovascular disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 44 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…There are no data about the relationship between apoCIII and MPO or PON1 in HDL. Our results show for the first time that apoCIII is increased in HDL 2 and HDL 3 (HDL 2 > HDL 3 ) from ACS compared to SA and N. The higher levels of apoCIII in HDL 2 compared to HDL 3 could be associated with the higher content of TG in HDL 2 versus HDL 3 , as was previously reported 41 . It is known that functional HDL inhibit or attenuate the oxidation of LDL and of the membrane phospholipids 18 , 42 .…”
Section: Discussionsupporting
confidence: 85%
“…There are no data about the relationship between apoCIII and MPO or PON1 in HDL. Our results show for the first time that apoCIII is increased in HDL 2 and HDL 3 (HDL 2 > HDL 3 ) from ACS compared to SA and N. The higher levels of apoCIII in HDL 2 compared to HDL 3 could be associated with the higher content of TG in HDL 2 versus HDL 3 , as was previously reported 41 . It is known that functional HDL inhibit or attenuate the oxidation of LDL and of the membrane phospholipids 18 , 42 .…”
Section: Discussionsupporting
confidence: 85%
“…There are data indicating that apo C3 directly provokes proinflammatory responses in vascular cells, including monocytes and endothelial cells. 31,32 The findings on association between circulating levels of PTX3 and measures of adiposity are inconsistent: some studies have found positive, whereas other have demonstrated inverse associations. [33][34][35] In our patients with T2D without NAFLD, positive association between PTX3 and waist circumference and BMI was found, while, interestingly, in patients with NAFLD such association did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…This hypertriglyceridemia-associated systemic inflammation can be reversed to varying degrees by administration of fibrates, resveratrol or omega-3 fatty acids [4244]. However, independent of triglyceride levels, apoCIII has inflammatory and cytotoxic effects [45]. For instance, purified human apoCIII enhances the attachment of monocyte-like cells to the human saphenous vein or coronary artery endothelial cells under both static and laminar shear stress conditions via induction of VCAM-1 [46].…”
Section: Discussionmentioning
confidence: 99%